SPEECH THERAPY CONSULTANCY FOR FAMILY MEMBERS OF PATIENTS WITH APHASIA - PAYLOZYAN, ZHANNA; DAVTYAN, SILVARD (Main Issues Of Pedagogy And Psychology, 2016)
The participation of the patient’s family with aphasia in the process of speech therapy is necessary and essential prerequisite for speech recovery. However, our society is not sufficiently informed about aphasia. As a result, the family members of a person with aphasia often do not know how to deal with a relative who has lost his/her speech. As a consequence, there is oftena misunderstanding regarding the patient’s activities and behavior. The essential content of the speech therapy consultancy with the family members of the patients with aphasia is introduced in the article. The authors stress the importance of providing information to the family members of people with aphasia, regarding aphasia symptoms and its overcoming features. Particularly it is mentioned, that aphasia is not an indication of a mental disorder or dementia. In case of aphasia, the social and speech isolation of a person who has lost his/her speech, is troubling. In the article, recommendations aimed at the establishment of contact between the patient and his/her relatives, as well as increasing the effectiveness of speech restoration process are introduced. Following the speech therapy recommendations will help the relatives to avoid common mistakes in the process of communication, which cause psychological harm. Taking into account the fact, that the speech restoration is a long-lasting process, the article also provides examples of assignments and exercises for supporting the speech restoration at home. The essential goal of speech therapy consultation is the establishment of speech-communication environment, which supports the restoration of speech and communication of patients with aphasia.